Simulasi Perubahan Tata Guna Lahan terhadap Laju Erosi Lahan Menggunakan Metode Universal Soil Loss Equation (USLE) pada Daerah Aliran Sungai (DAS) Ciseel - Hariati, Feril; Muhammad Libasut Taqwa, Fadhila; Alimuddin, Alimuddin; Salman, Nurcholis; Fadhillah Sulaeman, Nur Handika (University of Muhammadiyah Aceh, 2022)
One of the causes of the silting of the Sagara Anakan, estuary of Citanduy River is due to sedimentation caused by changes in land use, which causes the erosion rate to become uncontrollable. To predict the rate of surface erosion of the Ciseel watershed, one of Citanduy tributary, the USLE (Universal Soil Loss Equation) method was used, while the Geographic Information System was used to assist in the analysis of spatial data. The results of the analysis of the rate of erosion in the Ciseel watershed show that in 2006 it was 28 tons/ha/yr, in 2012 it was 44.2 tons/ha/yr and in 2016 it was 49.9 tons/ha/yr, so it belongs to the erosion hazard class II/mild. based on the USDA classification. From the results of this study, it can be shown that the rate of surface erosion in the Ciseel watershed has a small contribution to sedimentation in Sagara Anakan. The simulation of land use change as an effort to reduce the rate of erosion from dry agricultural land to rice fields is expected to reduce the rate of erosion up to 24.7% in 2016.